IDENTIFIKASI KOMPONEN AKTIF MINYAK ATSIRI DAUN Vitex trifolia, Linn YANG BERPERAN SEBAGAI PENOLAK SERANGGA TERHADAP Chrysomya sp. - Ami Soewandi J.S. (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1999)
Dried leaves powder of Vitex trifolia, Linn, is used tradisionally as insect repellent. The activity of the essential oil (isolated from the leaves) and this fractions were studied as a repellent against Chrysomya sp. Fraction E contained a single component and has proven as the most effective to repel Chrysomya sp. According to the spectra of UV, IR, and GC-MS analysis, the single component of fraction E was identified as 4-methyl-1-(methylethy)3-cyclohexnol.